LEGAL PROTECTION FOR MIDWIVES PROVIDING FIRST AID IN EMERGENCY SITUATIONS BASED ON LAW NUMBER 17 OF 2023 CONCERNING HEALTH - Hanafi, Doni; Asril, Juli; Pradita, Nugraha (Universitas Labuhanbatu, 2025)
The legal protection of midwives in providing emergency care, as regulated in Indonesia’s Health Law Number 17 of 2023, is essential for ensuring legal certainty and safety in medical practice. This study aims to analyze the scope of legal liability related to first aid provided by midwives to patients in emergency situations. Using a normative juridical approach and descriptive-analytical method, this research is based on literature reviews and secondary data from relevant laws and professional guidelines. The findings indicate that midwives are legally protected as long as their actions follow professional standards, codes of ethics, and standard operating procedures. Legal protection includes the right not to be criminally or civilly prosecuted when giving life-saving aid in emergencies within their competence, even if done beyond their normal authority—as long as it is based on scientific judgment and good faith. However, legal sanctions may apply if midwives act negligently, without proper competency or authority, or if harm is caused due to failure to follow procedures, such as not making timely referrals or conducting improper medical treatment. Illustrative cases show that midwives can face criminal charges (e.g., under Article 359 of the Criminal Code) or civil lawsuits when there is proven malpractice or patient death due to unprofessional conduct. This study emphasizes the need for clear legal frameworks supported by preventive mechanisms (such as continuous professional education), repressive actions (like disciplinary or criminal measures), and non-litigation efforts (such as mediation or institutional protection through professional associations) to ensure justice, safety, and legal clarity for midwives practicing in emergency contexts..Keywords: midwife; emergency care; legal protection; professional standards; regulation